Family business succession process: A case study of Fravizel S.A - Santos, Eva Linda Silva dos (2019)
This study aims to understand the Succession Process and comprehend what could be the future of the organization, when the potential successors starts their role in the leadership of the Family Business. To do so, it was conducted a research on Family Businesses and the relation with the Succession Process, as a crucial moment for the business future. The research method is the case study, having been conducted an interview with the founder and the possible successor. After the analysis, the succession process of Fravizel S.A was draw. Through this analysis it was possible to observe some aspects of the company’s future. The value of this research lies in analyzing the Succession process as a crucial moment in a Family Business life which a different person from the founder will act in order for the business to continue with success, without compromising the future generations and the family harmony.